God & morality : four views - Loftin, R. Keith, 1981-; Fales, Evan, 1943- (Downers Grove, Ill. : IVP Academic, 2012)
In God and Morality: Four Views, first-rate philosophers take on a hotly contested topic. Here we listen in on a discussion between four distinguished contributors that puts on display the current divide between naturalism and theism.
Naturalist moral realism / Evan Fales -- Naturalist moral nonrealism / Michael Ruse -- Moral essentialism / Keith E. Yandell -- Moral particularism / Mark D. Linville.
Includes bibliographical references and index.
Keywords: Christian ethics; Ethics